Tren Penelitian: Pendekatan STEAM dalam Pembelajaran Sains - Muhammad Ikhbar Ihsan; Parno; Purbo Suwasono (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to examine research trends and explore the potential use of the STEAM approach in science learning. A Systematic Literature Review (SLR) was conducted using the PRISMA guidelines. The keywords “STEAM” and “Science Learning” were used to search the Scopus database, resulting in 60 articles, of which 13 met the inclusion criteria for further analysis. The findings highlight that the STEAM approach has strong potential to enhance science learning, particularly in improving students’ 21st-century skills, conceptual understanding, and engagement through contextual and interdisciplinary learning experiences. This study is expected to serve as a valuable reference for researchers and educators in developing effective STEAM-based instructional strategies across various educational levels.